Efficacy, acceptability, and safety of antidepressants for low back pain: a systematic review and meta-analysis - Michael C. Ferraro (Systematic Reviews, 2021)
Abstract Background Antidepressant medicines are used to manage symptoms of low back pain. The efficacy, acceptability, and safety of antidepressant medicines for low back pain (LBP) are not clear. We aimed to evaluate the efficacy, acceptability, and safety of antidepressant medicines for LBP. Methods We searched CENTRAL, MEDLINE, Embase, CINAHL, ClinicalTrials.gov , the EU Clinical Trials Register, and the WHO International Clinical Trial Registry Platform from inception to May 2020. We included published and trial registry reports of RCTs that allocated adult participants with LBP to receive an antidepressant medicine or a placebo medicine. Pairs of authors independently extracted data in duplicate. We extracted participant characteristics, study sample size, outcome values, and measures of variance for each outcome. We data using random-effects meta-analysis models and calculated estimates of effects and heterogeneity for each outcome. We formed judgments of confidence in the evidence in accordance with GRADE. We report our findings in accordance with the PRISMA statement. We prespecified all outcomes in a prospectively registered protocol. The primary outcomes were pain intensity and acceptability. We measured pain intensity at end-of-treatment on a 0–100 point scale and considered 10 points the minimal clinically important difference. We defined acceptability as the odds of stopping treatment for any reason. Results We included 23 RCTs in this review. Data were available for pain in 17 trials and acceptability in 14 trials. Treatment with antidepressants decreased pain intensity by 4.33  points (95% CI − 6.15 to − 2.50) on a 0–100 scale, compared to placebo. Treatment with antidepressants increased the odds of stopping treatment for any reason (OR 1.27 [95% CI 1.03 to 1.56]), compared to placebo. Conclusions Treatment of LBP with antidepressants is associated with small reductions in pain intensity and increased odds of stopping treatment for any reason, compared to placebo. The effect on pain is not clinically important. The effect on acceptability warrants consideration. These findings provide Level I evidence to guide clinicians in their use of antidepressants to treat LBP. Trial registration We prospectively registered the protocol for this systematic review on PROSPERO ( CRD42020149275 ).